PENGARUH IMPLEMENTASI SISTEM ENTERPRISE RESOURCE PLANNING (ERP), BUDAYA KERJA DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI PEMODERASI PADA PERUSAHAAN ALAS KAKI DI PT. PRATAMA ABADI INDUSTRI - Susilawati, Ari; Rustandi, Tata; Suadma, Udin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the declining performance of the footwear industry,which requires companies to improve the effectiveness of human resourcemanagement and operational systems. The purpose of this study is to analyze theeffect of Enterprise Resource Planning (ERP) implementation, work culture, andleadership on employee performance with work motivation as a moderating variableat PT. Pratama Abadi Industri. The study used a quantitative approach with a surveymethod by distributing questionnaires to 220 employees determined using theRoscoe method. Data were analyzed using Structural Equation Modeling–PartialLeast Square (SEM-PLS). The results showed that ERP implementation, workculture, and leadership had a positive and significant effect on employeeperformance. However, work motivation was not proven to moderate the effect ofERP implementation, work culture, and leadership on employee performance. Thisfinding indicates that employee performance improvements are more influenced bydirect system optimization and managerial practices than by the role of motivationas a moderating variable. The results of this study are expected to be aconsideration for company management in formulating policies to improveemployee performance. In addition, this study can be a reference for furtherresearch related to human resource management.Keywords: ERP, work culture, leadership, employee performance